P005 A two-night randomised controlled cross-over trial of AVAPS AE auto-titrating bi-level ventilation vs standard in-lab titration in patients with motor neurone disease commencing overnight ventilatory support. (9th November 2022) - Aiyappan, V; Catcheside, P; Grivell, N; Hansen, C; Keighley James, G; Schultz, D; Allcroft, P
Abstract: Introduction: Sleep disordered breathing in motor neurone disease (MND) is heterogeneous. Auto-adjusting AVAPS-AE mode of non-invasive ventilation (NIV) could simplify NIV setup and use in MND. This pilot study assessed NIV titration and longer-term outcomes with AVAPS AE auto-pressure support versus standard S/T mode NIV titration in patients with MND. Methods: 10 MND patients commencing NIV consented to a 2 consecutive night randomised controlled cross-over trial of auto-titrating AVAPS-AE versus standard S/T mode NIV titrated according to current clinical practice. Patients underwent in-laboratory polysomnography (PSG) on both nights before continuing on the second allocated mode of NIV. Results: 8 patients completed both cross-over nights and 9 subsequently continued on home NIV (4 on S/T and 5 on AVAPS-AE mode). Compared to baseline, both S/T and AVAPS-AE modes significantly reduced apnea hypopnea index (AHI; mean [95%CI] 14.8 [6.8-22.8] to 1.2 [0-2.7] and 3.6 [0-7.1] /h respectively), with no significant differences between modes on other PSG outcomes. Maximum EPAP (15.4 [13.4-17.4] vs 8.3 [4.9-11.6] cmH2O, p=0.003) and pressure support levels (16.3 [11.2-21.3] vs 6.6 [5.9-7.4] cmH2O, p=0.003) were higher with AVAPS-AE versus S/T mode respectively, although average pressure support levels were not different. Over 6 months of follow-up, average daily use was similar in both treatment groups (AVAPS-AE 7.3 [3.2-11.3]; S/T mode 7.8 [3.5-12] h/day). Conclusion: Automated AVAPS-AE mode of BiPAP support appears to achieve similar control of sleep disordered breathing when compared to standard S/T mode, and to be well tolerated and used in patients with MND.